The Effect of Experiential Marketing, Service Quality and Corporate Image on Customer Loyalty Expands with Customer Satisfaction as Intervening Variables at PT. Permodalan Nasional Madani Regional Solo - Sapta Irwanto; A. Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of experiential marketing, service quality, corporate image on customer loyalty through customer satisfaction Mekaar PT. Solo Regional Civil National Capital. This study uses a quantitative approach with Structural Equation Modeling (SEM) using the PLS program. and IBM Statistics SPSS 26.0. The unit of analysis used is customer Mekaar of PT. Permodalan Nasional Madani Solo Regional. The sample consists of 120 respondents. The data collection technique was carried out using a questionnaire distributed online. The results showed that customer satisfaction can mediate the effect of experiential marketing, service quality, and corporate image on customer loyalty of customer Mekaar of PT. Permodalan Nasional Madani Solo Regional